ANALISIS KEMAMPUAN REPRESENTASI MATEMATIS SISWA KELAS VIII DALAM MENYELESAIKAN SOAL MATEMATIKA PADA MATERI BANGUN RUANG - Muhamad Iqbal Ramadhan; Indrie Noor Aini (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The purpose of this study was to describe the mathematical representation ability of eighth grade junior high school students in solving math problems on the material of spatial structure. This research is a qualitative descriptive research. The subjects in this study were class XIII students at SMP Islam Telukjambe for the academic year 2020/2021 as many as 3 students. The focus of this research is the ability of visual representation, symbolic representation, and verbal representation. The research methodology used is descriptive qualitative where tests and interviews are data collection techniques used. The conclusion of this study is that the ability of mathematical representation is very important to be mastered by students in determining the right strategy to be able to solve a mathematical problem. Mathematical problems in everyday life, visual, verbal and symbolic representation skills are used, because everyday life problems need to be represented in the form of symbols or images in order to make it easier to solve problems and be faced.